2020
DOI: 10.1088/1742-6596/1622/1/012105
|View full text |Cite
|
Sign up to set email alerts
|

Opto-Electronic Properties of Methyl-Ammonium Lead Halide: A First Principle Approach

Abstract: Using first principle approach, based on Density functional theory (DFT), we have investigated the ground state opto-electronic properties of methyl-ammonium lead halide (MLH). CH3NH3PbX3 where (X=Cl, Br, I), the key materials for opto-electronic applications, especially for efficient and low cost solar cell. The halide contents are important in electronic and optical behavior such as band structure, density of states, absorption, optical conductivity etc. The nature of calculated band structure (BS) and densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They concluded that all the compounds are semiconductors with band gaps of 1.98 eV, 2.36 eV and 2.78 eV for CH 3 NH 3 PbI 3 , CH 3 NH 3 PbBr 3 and CH 3 NH 3 PbCl 3 , respectively. The compound CH 3 NH 3 PbI 3 has a narrow band gap and is assumed to be the best candidate for optoelectronic applications [13]. The transition metal ions (TMI) at B and B′ in the DPS show a wide range of magnetic and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that all the compounds are semiconductors with band gaps of 1.98 eV, 2.36 eV and 2.78 eV for CH 3 NH 3 PbI 3 , CH 3 NH 3 PbBr 3 and CH 3 NH 3 PbCl 3 , respectively. The compound CH 3 NH 3 PbI 3 has a narrow band gap and is assumed to be the best candidate for optoelectronic applications [13]. The transition metal ions (TMI) at B and B′ in the DPS show a wide range of magnetic and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The valence band and conduction bands are mostly occupied by halides and lead orbitals respectively. The overall CH3NH3PbI3 is most suitable material for organic solar cells device [21].…”
mentioning
confidence: 99%